Animation in Transition: A semiotic reading of Ase Mmanwu Masquerade Costume in Performance. - umukoro, julie (Advances in Social Sciences Research Journal, 2015)
The study takes a critical look at costume in motion. Motion or movement here imposes on costume the image of a living object and as such a composition drawn on a symbiotic relationship between anarticle of material culture and an animator; usually a human factor. This thus infers that, it is in the conjugal relationship of performer and costume that the performancecostume attains full realization and finally, a scaling up in its utility value. The study addresses critically, the Ase Mmanwu costume in performance. As tool to aid artistic exhibition, the Mmanwu costume in performance comes alive as a rich semiotic field explored for signification in the Ase Mmanwu art. The brand, embodied in spatial movements and convolutions, creates and imposes strictly the image of an animated and highly reflexive object which lingers in the consciousness of its beholder(s) long after its perception. With special interest in the masking components of Ase Mmanwu tradition, this discourse is restricted to the animated and antiquated costume of theMmanwumasquerade of Ase people of Nigeria.